2009
DOI: 10.1021/jf804004z
|View full text |Cite
|
Sign up to set email alerts
|

Triple Concentrated Tomato Paste: Discrimination between Italian and Chinese Products

Abstract: (1)H NMR spectroscopy was applied to discriminate triple concentrated tomato paste coming from two different countries. Notwithstanding different tomato cultivars and ripening stages employed to obtain the final product, significant discrimination between Italian and Chinese samples was obtained by combining NMR data and principal component analysis. Supervised orthogonal projection to latent structure discriminant analysis (OPLS-DA) technique was used to build robust classification models, while S-plot was em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 35 publications
(45 reference statements)
2
33
0
Order By: Relevance
“…Recently, Consonni et al (2009) showed that 1 H NMR spectroscopy is useful for discriminating triple concentrate tomato paste coming from Italy and China, confirming significant discrimination. Citrate (and not other parameters like lycopene, particularly affected by the processing and the storage) was identified as the most relevant parameter for discrimination, followed by some amino acids (aspartate and glutamine) and sugars.…”
mentioning
confidence: 92%
“…Recently, Consonni et al (2009) showed that 1 H NMR spectroscopy is useful for discriminating triple concentrate tomato paste coming from Italy and China, confirming significant discrimination. Citrate (and not other parameters like lycopene, particularly affected by the processing and the storage) was identified as the most relevant parameter for discrimination, followed by some amino acids (aspartate and glutamine) and sugars.…”
mentioning
confidence: 92%
“…The complexity of NMR data in food metabolomics studies is clearly the primary impetus for the coupling of NMR spectroscopy with multivariate statistical methods, capable of gathering samples with similar features Tomassini, Capuani, Delfini, & Miccheli, 2013). Among them, supervised methods that may enhance classification performance, such as orthogonal projection to latent structures -discriminant analysis (OPLS-DA) and its bidirectional modifications (O2PLS-DA) (Bylesjö, Rantalainen, Cloarec, Nicholson, Holmes, & Trygg, 2006), have shown great potential to determine the authenticity of various foodstuffs, mainly on the basis of their geographical or botanical origin (Consonni, Cagliani, & Cogliati, 2012a, 2012bConsonni, Cagliani, Stocchero, & Porretta, 2009Fotakis et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, two studies were dealing with the determination of geographical origin of cherry tomatoes (Sequi, Dell'Abate, & Valentini, 2007) and triple concentrated tomato pastes (Consonni, Cagliani, Stocchero, & Porretta, 2009) by 1 H-NMR spectroscopy. Moreover, our research group has demonstrated that the multi element profiling obtain using ICP-MS followed by a suitable statistical treatment of data can be successfully used in this type of investigation (Lo Feudo et al, 2010).…”
Section: Introductionmentioning
confidence: 99%